Products From Olive Tree 2016
DOI: 10.5772/64736
|View full text |Cite
|
Sign up to set email alerts
|

Pigments in Extra‐Virgin Olive Oil: Authenticity and Quality

Abstract: Pigments, divided into carotenoids and chlorophyll derivatives, are responsible for the colour of extra-virgin olive oil (EVOO). The concentration of pigments in EVOO depends on several factors, such as the maturity of olives before oil production, the cultivar and the geographic origin of olives. Pigments naturally degrade in olive oil (OO) during storage, and they may decompose due to light, temperature and oxygen exposure. The nature and concentration of pigments in EVOOs are different from seed oils, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…Previous studies (Roca, & Minguez-Mosquera, 2001) reported that this ratio decreases, depending on the ripeness stage, in table olives, but in olive oils it remains constant around the value of 1.14, shifting in the range 0.53  1.40. Our study, however, shows that this ratio can assume values in a much larger range, in agreement with other works (Psomiadou & Tsimidou, 2001;Criado et al, 2007;Aparicio-Ruiz, Gandul-Rojas & Roca, 2009;Lazzerini, Cifelli & Domenici, 2016;Lazzerini & Domenici 2017).…”
Section: Pigments' Content In Evoos Produced In Different European Cosupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies (Roca, & Minguez-Mosquera, 2001) reported that this ratio decreases, depending on the ripeness stage, in table olives, but in olive oils it remains constant around the value of 1.14, shifting in the range 0.53  1.40. Our study, however, shows that this ratio can assume values in a much larger range, in agreement with other works (Psomiadou & Tsimidou, 2001;Criado et al, 2007;Aparicio-Ruiz, Gandul-Rojas & Roca, 2009;Lazzerini, Cifelli & Domenici, 2016;Lazzerini & Domenici 2017).…”
Section: Pigments' Content In Evoos Produced In Different European Cosupporting
confidence: 93%
“…Quantification of pigments in EVOOs and their relationship with quality parameters, however, is not an easy task (Lazzerini, Cifelli, & Domenici, 2016). The amount of a single pigment and the relative content in carotenoids and chlorophyll derivatives strongly depend on the olive varieties and geographic origin (Gandul-Rojas & Minguez-Mosquera, 1996;Giuffrida et al, 2007;Aparicio-Ruiz, Gandul-Rojas & Roca, 2009;Pizarro et al, 2013), the maturation of olives at the time of harvesting (Cevik et al, 2014), the extraction process (Gallardo-Guerrero, Roca & Minguez-Mosquera, 2002) and the storage conditions (Gambacorta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds, α-tocopherol and β-carotene are reported as the main groups of compounds with antioxidant properties that correlated to the oxidative stability of virgin olive oils [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies utilised pigments such as carotenoids and chlorophyll derivatives in extra-virgin olive oil as parameters/index of authenticity and quality. Pigments in oil matrices can be identified and quantified by chromatographic techniques after a pretreatment of the samples such as extraction and/or saponification, or by spectroscopic techniques without pretreatment of the samples [111]. Another work by the same authors quantified the main pigments, i.e., ß-carotene, lutein, pheophytin A, and pheophytin B, in several extra-virgin olive oils produced from a blend of three cultivars (Moraiolo, Frantoio, and Leccino) typical of Tuscany (Italy) in three different years.…”
Section: Phenolic Compounds Tocopherols and Squalenesmentioning
confidence: 99%